Smart integration of drive system for induction motor applications in electric vehicles - Mohamed K. Metwaly; Mohamed Alsharef; Nehmdoh A. Sabiha; Ehab E. Elattar; Ibrahim B. M. Taha; Amr M. Abd-Elhady; Nagy I. Elkalashy (Institute of Advanced Engineering and Science, 2021)
In this paper, a smart drive system of the induction motor (IM) is proposed and adapted for applications in electric vehicles (EVs). Objectively, the EV drive systems are robust over wide speed and torque ranges. The proposed drive system is independent of encoder (encoderless) and concerned with the torque control drive (TCD) and indirect rotor field-oriented control (IRFOC) using the sliding mode observer (SMO). This arrangement of monitoring system and control techniques are smartly integrated for the IM applications in EVs. The encoderless technique utilizes SMO to estimate the stator current, rotor flux angle, and rotor speed. The SMO is verified in motoring mode at very low and zero speed conditions. The accelerator pedal is utilized for TCD to generate the reference torque required to accelerate the EV by the driver. The rotor flux angle is estimated based on IRFOC method. The laboratory waveforms illustrate the robustness of the encoderless control of the IM-based torque control drive system in electrical vehicle applications at very low speed using SMO. The laboratory waveforms prove the validity of SMO with encoderless control of a smart dive system of the IM in EV applications under load torque/speed variations.